Aplikasi Teknologi Sistem Informasi Dalam Pengelolaan Sumberdaya Air - Atika Lubis (Institut Teknologi Bandung, 2002)
Manual and conventional information provider nowadays, seems to be insufficient compared to the acceleration of information technology development. The use of information system technology directly supports the development activities, especially in planning and managing the water resources. Water resources belong to the natural resources and the existence tends to be limited. This evidence can be proved in some big cities in Indonesia, such as Java, Bali, are now in critical conditions. If these conditions are conducted continuously without the effort to manage, in the future will occur water deficiency conditions. Application of integrated information system, continuously, the effort of updating data and data compilation of data and water carrying capacity, is effective solution, and the cost is relatively cheaper in planning and managing the water resources.